Nd and Sr Isotopes and REE Investigation in Tropical Weathering Profiles of Amazon Region - Horbe, Adriana Maria Coimbra; Albuquerque, Márcio Fernando Dos Santos; Dantas, Elton Luiz (Frontiers in Earth Science, 2022)
The exceptional development of lateritic profiles make the Amazon one of the best places to conduct a refined study on the effects of long-term tropical climate on the Earth's surface rocks. Concentrations of Nd and Sr isotopes, as well as rare earth elements (REE), Sr, and other trace elements were determined in six profiles in order to shed new light into element behavior and into the processes controlling the geochemistry and the transfer of these elements among the different compartments of the critical zone. Our investigation indicates natural isotope regional pulse transformations in the Oxisol at the top of all profiles. The ƐNd(t=0) values of the parent rock, mottled horizon, and lateritic duricrust are radiogenic similar to the Amazon craton signature. The thick Oxisol has ƐNd(t=0) values which are much more radiogenic and less variable, whereas it has Zr, Th, Y, and REE in higher concentrations. These issues highlight a complex process for the Nd system, and the following possibilities are proposed to explain this behavior: formation of authigenic cerianite and/or kaolinite, penetration of low-temperature weathering solutions along zircon fractures, and some vegetation uptake. These possibilities allow keeping the more radiogenic Nd isotopes, whereas the less radiogenic Nd is released especially in the Oxisol after REE mineral(s) weathering. The Sr system contrary to that of Nd became less radiogenic along the profiles and relatively to the parent rocks content, because nearly all Sr was removed after K-Rb feldspar and mica weathering. However, a mixture return of less radiogenic Sr from plant, biogenic aerosol, and rainwater may have helped let the weathering profiles become less radiogenic. These characteristics let the Oxisol even less Sr radiogenic but still permitting to identify the general parent rocks signature. In contrast, Nd is highly fractionated in the Oxisol relative to the parent rock. Thus, the REE and Sr behavior, similar in the six profiles, does not necessarily reflect only the parent rock geochemistry, but it also depends on the multiple surficial processes typical of the critical zone: weathering, pedogenesis, plant root activity, and rainwater composition which change the inherited primary minerals isotope signatures.